Interventionist classroom management and learning of children with disabilities in primary schools: An inclusive and reframing approach - Matovu, Musa; Nakayiza, Aidah (My University, 2019)
The study aimed at examining the relationship between interventionist classroom management and learning of pupils with disabilities in primary schools. The objectives of the study were; (i) to examine the relationship between teacher proximity and learning of pupils with disabilities in primary schools, (ii) to analyze the relationship between relationship building and learning of pupils with disabilities in primary schools, and (iii) to examine the relationship between sitting arrangement and learning of pupils with disabilities in primary schools. A cross sectional survey research design was used to obtain information from 135 respondents. A questionnaire, interview guide and focus group discussion template were used as tools to collect data for the study. Quantitative and qualitative data collected was analyzed using the Statistical Package for Social Sciences (SPSS) and thematic content analysis respectively. Pearson product moment correlation coefficient results showed that a positive statistically significant relationship existed between teacher proximity and learning of pupils with disabilities (r = .69, n = 135, p < .01), a positive statistically significant relationship with relationship building (r = .52, n = 135, p < .01) and sitting arrangement (r = .38, n = 135, p < .01). It was concluded that teacher proximity has the highest statistically significant effect with learning of pupils with disabilities. Relationship building has a moderate statistically significant effect on the learning of pupils with disabilities. Sitting arrangement has the least statistically significant effect with learning of pupils with disabilities. It is recommended that teacher proximity, relationship building and sitting arrange should be considered when using interventionist classroom management for better learning of the disabled pupils.
Keywords: Interventionist classroom management; Disabled children; Inclusion; Reframing